2012
DOI: 10.1103/physrevlett.109.223902
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Vibrational Modes in SingleSiO2Nanoparticles Using a Tunable Metal Resonator with Optical Subwavelength Dimensions

Abstract: Using a tunable optical subwavelength microcavity, we demonstrate controlled modification of the vibronic relaxation dynamics in a single SiO(2) nanoparticle. By varying the distance between the cavity mirrors we change the electromagnetic field mode structure around a single nanoparticle and the radiative transition probability from the lowest vibronic level of the electronically excited state to the progression of phonon levels in the electronic ground state. We demonstrate redistribution of the photolumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…However, our recently developed nanocavity-based method of QY determination measures only the cavity modulated radiative decay rate of an emitter, which makes it also applicable for such complex systems as SiO 2 NPs 28, 29 . Placing SiO 2 NPs between the metal mirrors of a nanocavity changes their emission behavior due to a cavity-modified electromagnetic field mode density 8,30,31 . Because the cavity changes only the radiative rate of the embedded emitters, measuring the modulation of the PL lifetime as a function of the cavity length allows for determining an absolute value of an emitters' QY 32 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our recently developed nanocavity-based method of QY determination measures only the cavity modulated radiative decay rate of an emitter, which makes it also applicable for such complex systems as SiO 2 NPs 28, 29 . Placing SiO 2 NPs between the metal mirrors of a nanocavity changes their emission behavior due to a cavity-modified electromagnetic field mode density 8,30,31 . Because the cavity changes only the radiative rate of the embedded emitters, measuring the modulation of the PL lifetime as a function of the cavity length allows for determining an absolute value of an emitters' QY 32 .…”
Section: Resultsmentioning
confidence: 99%
“…A typical example of an emitter that is chemically bound to a matrix is a luminescent centre in a SiO 2 nanoparticle (NP) 7,8 . It has been shown that the PL from SiO 2 structures in the visible spectral range arises from non-bridging oxygen centres [9][10][11] , neutral oxygen vacancies 11,12 , and hydrogen-related species 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] This so-called Purcell effect has been measured for fluorophores placed between two gold nanoparticles, [17] close to a dielectric interface, [19,18] a metallic mirror, [20][21][22] or a sharp tip of a scanning probe microscope. [23,24] An efficient way of changing the LDOS of the electromagnetic field is to embed an emitter into a plane-parallel optical resonator, [25][26][27][28][29][30] which allows for precise control of the LDOS by varying the cavity length. Moreover, this length can be precisely monitored by measuring the cavity's transmission spectrum, which eliminates potential systematic errors caused by mechanical instabilities of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Using a tuneable optical micro-resonator with subwavelength spacing, we demonstrate controlled modulation of the radiative transition rate of a single molecule, which is measured by monitoring its fluorescence lifetime [4]. By comparing the experimental data with a theoretical model, we extract both the pure radiative transition rate as well as the quantum yields of individual molecules.…”
Section: Resultsmentioning
confidence: 99%